Media Learning-Based Multimedia for Eye Studying Multimedia - Rawis, Joulanda A.M.; Lengkong , Jeffry Sony Junus; Namsa, Johanis P.; Tendean, Sherly D.; Manumpil, Yulit B. (International Journal of Information Technology and Education, 2023)
Study This is a study development media learning That aims To produce media learning eye studying Multimedia Which is expected can help in the process of Study teaching. Research This is a study development of the Multimedia Development Life Cycle (MDLC). In the method, 6 (six) stages are (1) Concept, (2) design, (3) Obtaining Content Material, (4) Assembly, (5), Testing, and (6) Distribution. On stage In this testing or testing phase, there are four forms of testing, namely Developer Tests, Expert Media, Expert Material, and End-user Tests. From study obtained good results, and from these results, the research drew conclusions that media applications learning multimedia.